(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2026)
Dental caries remains one of the most common dental pathologies, despite significant advances in prevention and treatment. Modern caries therapy is aimed not only at restoring the anatomical shape of the tooth, but also at preserving the viability of hard tissues, preventing secondary caries and ensuring the biological compatibility of filling materials. In this context, glass ionomer cements (CC) occupy a special place due to their ability to chemically bind to tooth tissues, release fluoride and provide an anti-carious effect. The article discusses the properties, mechanisms of action and clinical significance of glass ionomer cements in the treatment of dental caries, as well as their advantages and limitations in comparison with other filling materials.